CinemaScope and the close-up/montage style: new solutions to familiar problems. Issue 2 (3rd April 2019) - Roggen, Sam
ABSTRACT: This article searches empirical support for the elimination of close-ups and fast cutting in early American CinemaScope films (1953–1959). While these transformations were commented upon extensively when the new anamorphic widescreen process arrived, this study claims that Hollywood in fact bent the technology to fit its existing production methods and stylistic norms. Adopting a historical-analytical poetics of cinema, it commences with an examination of the earliest reactions to CinemaScope. The article not only addresses such primary sources as production files and trade papers, but also looks at the first critical journals that devoted attention to the new process. This research focuses on a number of statements with regard to close-ups and editing that dominated the discourse on CinemaScope style. It will analyze these by combining two methodological approaches. Firstly, this article systematically measures such stylistic parameters as shot length and shot scale. Building on Barry Salt's data-driven style analyses, it confronts new digital measurements with existing datasets. Secondly, it adopts David Bordwell's problem/solution model in order to study the various solutions filmmakers developed in response to the changed conditions of filmmaking in CinemaScope, with particular attention for stylistic problems related to close shots and editing.